Treatment patterns and clinician stress related to care of out-of-hospital cardiac arrest patients with a do not attempt resuscitation order - Ryo Tanabe; Takashi Hongo; Takafumi Obara; Tsuyoshi Nojima; Atsunori Nakao; Jonathan Elmer; Hiromichi Naito; Tetsuya Yumoto (Resuscitation Plus, 2023)
Objective: This research investigated treatment patterns for out-of-hospital cardiac arrest patients with Do Not Attempt Resuscitation orders in Japanese emergency departments and the associated clinician stress. Methods: A cross-sectional survey was conducted at 9 hospitals in Okayama, Japan, targeting emergency department nurses and physicians. The questionnaire inquired about the last treated out-of-hospital cardiac arrest patient with a Do Not Attempt Resuscitation. We assessed emotional stress on a 0–10 scale and moral distress on a 1–5 scale among clinicians. Results: Of 208 participants, 107 (51%) had treated an out-of-hospital cardiac arrest patient with a Do Not Attempt Resuscitation order in the past 6 months. Of these, 65 (61%) clinicians used a “slow code” due to perceived futility in resuscitation (42/65 [65%]), unwillingness to terminate resuscitation upon arrival (38/65 [59%]), and absence of family at the time of patient’s arrival (35/65 [54%]). Female clinicians had higher emotional stress (5 vs. 3; P = 0.007) and moral distress (3 vs. 2; P = 0.002) than males. Nurses faced more moral distress than physicians (3 vs. 2; P < 0.001). Adjusted logistic regression revealed that having performed a “slow code” (adjusted odds ratio, 5.09 [95% CI, 1.68–17.87]) and having greater ethical concerns about “slow code” (adjusted odds ratio, 0.35 [95% CI, 0.19–0.58]) were associated with high stress levels. Conclusions: The prevalent use of “slow code” for out-of-hospital cardiac arrest patients with Do Not Attempt Resuscitation orders underscores the challenges in managing these patients in clinical practice.